2020
DOI: 10.1093/pch/pxaa015
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the current state of medical education on cannabis in Canada: Preliminary findings from Quebec

Abstract: The legalization of recreational cannabis across Canada has revealed the importance of medical education on cannabis-related topics. A recent study has indicated that Canadian physicians report a significant gap in current versus desired knowledge regarding the therapeutic use of cannabis. However, the state of education on cannabis has never been studied in Canadian medical schools. This article presents the preliminary findings of a survey conducted to understand the perceptions of Quebec’s medical students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Given the most commonly selected reasons for MC use in this survey (cancer or terminal-illness related symptoms and intractable pain) this may ideally take place during training in fields such as family medicine, palliative care, and pain management. This process could be facilitated by the creation of standardized teaching materials as well as the inclusion of cannabis-specific learning objectives in licensing exams and in the curricula of accreditation committees like the Committee on Accreditation of Canadian Medical Schools [ 15 , 19 ]. Our results suggest that increased training, as in Group D, correlates with a stronger feeling of comfort in knowledge of, counselling on, and prescribing MC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the most commonly selected reasons for MC use in this survey (cancer or terminal-illness related symptoms and intractable pain) this may ideally take place during training in fields such as family medicine, palliative care, and pain management. This process could be facilitated by the creation of standardized teaching materials as well as the inclusion of cannabis-specific learning objectives in licensing exams and in the curricula of accreditation committees like the Committee on Accreditation of Canadian Medical Schools [ 15 , 19 ]. Our results suggest that increased training, as in Group D, correlates with a stronger feeling of comfort in knowledge of, counselling on, and prescribing MC.…”
Section: Discussionmentioning
confidence: 99%
“…Many HCPs in Canada may not be familiar with CBM due to the lack of coverage of this topic in professional school. Studies assessing medical education in Canada and around the world have found that most trainees have minimal exposure to CBM-related topics in their curricula [15][16][17][18]. With strong media and public interest surrounding CBM, HCPs are likely to be asked more questions about the topic.…”
Section: Discussionmentioning
confidence: 99%
“…Canadian youth (aged [15][16][17][18][19][20][21][22][23][24] have one of the highest rates of cannabis use worldwide 1 2 with prevalence rates that are almost double that of adults. Recent data indicate that 44% of youth aged [16][17][18][19], and 51% of youth aged 20-24, report past year cannabis use versus 21% of adults over the age of 25.…”
Section: Introductionmentioning
confidence: 99%
“…18 19 Service providers also have gaps in knowledge about cannabis use in youth and need more education and training. 20 21 A recent survey conducted in the USA where 11 states have legalised recreational cannabis use found variation and gaps in service providers' knowledge and beliefs on cannabis. Many service providers described discomfort discussing cannabis use with clients.…”
Section: Introductionmentioning
confidence: 99%
“…Canadian youth have a wide range of beliefs about recreational cannabis use, and many have misconceptions and lack information about the risks and harms associated with cannabis use 18 19. Service providers also have gaps in knowledge about cannabis use in youth and need more education and training 20 21. A recent survey conducted in the USA where 11 states have legalised recreational cannabis use found variation and gaps in service providers’ knowledge and beliefs on cannabis.…”
Section: Introductionmentioning
confidence: 99%